The Concept of Critical Thinking in the Quran: A Study of the Story of Qabil and Habil in Tafsir Al-Misbah - Setiawan, Setiawan; Ibrahim, Muhammad Syahrial Razali (Electronic Journal of Education, Social Economics and Technology, 2024)
The Qabil and Habil incidents are the first murder events that have happened to humans that have been told in the Quran, but nevertheless there are many life lessons that can be learned from these events. This study aims to describe the analysis of the study of the interpretation of Al-Misbah Surah Al-Maidah verses 27-31. The research method uses a qualitative approach with text analysis. The results of the study, which is a study of the tafsir of Al-Misbah by Quraish Shihab, show that the events of Qabil and Habil are full of dialogue between the two humans. Based on the dialogue, it can be concluded that: 1) The ability to think critically is able to analyze the information obtained from observation and produce a decision in solving problems. 2) Critical thinking skills can affect the emotional intelligence of oneself and others, 3) Critical thinking skills can evaluate all more objective information, 4) Critical thinking skills are able to assess, critically and develop more logical ideas. However, one of the factors that hinders a person from thinking critically is the instability of emotional control.